KELIMPAHAN CHRYSOPHYTA PADA MEDIA BUDIDAYA IKAN NILA YANG DIBERI PAKAN FERMENTASI DENGAN PENAMBAHAN TEPUNG KULIT UBI KAYU DAN PROBIOTIK - Retno Ambarwati; Endang Widyastuti; Dwi Sunu Widyartini (Scripta Biologica, 2014)
Chrysophyta is also known as golden-yellow algae because of the yellow dominant pigment of carotene and xanthophyll. This study aimed to determine species richness and abundance of Chrysophyta in the Tilapia culture media which was fed with the addition of cassava peel flour and probiotic. The method applied in this study was the experimental method with 4 treatments, i.e.: the use of fermented feed with the addition of cassava peel flour (0%, 25%, 50%, and 75%) and probiotic in Tilapia culture media. Each treatment was replicated 4 times. Sampling was carried out 6 times at intervals of 2 weeks. The observed parameters were the main parameters, i.e.: the number of Chrysophyta species and individuals; and supporting parameters, i.e.: water temperature, pH, TDS, TSS, NO3, NO2, BOD5, DO, and total of phosphate. Species richness and abundance of Chrysophyta data were analyzed using cluster analysis based on Bray-Curtis similarity coefficient. The analysis continued with Similarity Percentages (SIMPER) analysis to determine the contribution of species to the similarity index in each group or to dissimilarity index amongst groups. The results showed that the species richness found in the Tilapia media culture which was fed with the addition of cassava peel flour and probiotic consist of 20 species belonging to a class namely Bacillariophyceae. Abundance of Chrysophyta obtained was ranged from 5.160-13.292 individuals/liter. The cluster analysis showed that Chrysophyta amongst treatments have a quite high similarity level (> 50%) was ranged between 65.56% -83.99%. Contributions of species which contribute the highest similarity index were Diatoma vulgare (49.80%), Navicula brachysira (70.50%) and Navicula platystoma (82%).